Pemikiran Pembaharuan Pendidikan K.H Ahmad Dahlan di Indonesia: Penelitian - Yusril (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Educational reform in Indonesia is inextricably linked to the figure of K.H. Ahmad Dahlan, through the Muhammadiyah organization. The founding goal of Muhammadiyah was to interpret the verses of the Qur'an, first revealed through the Prophet Muhammad. With the word